Single-cell transcriptome sequencing reveals Wolbachia-mediated modification in early stages of Drosophila spermatogenesis. Issue 1990 (11th January 2023) - Dou, Weihao; Sun, Baofa; Miao, Yunheng; Huang, Dawei; Xiao, Jinhua
Abstract : Wolbachia are the most widely distributed intracellular bacteria, and their most common effect on host phenotype is cytoplasmic incompatibility (CI). A variety of models have been proposed to decipher the molecular mechanism of CI, among which the host modification (HM) model predicts that Wolbachia effectors play an important role in sperm modification. However, owing to the complexity of spermatogenesis and testicular cell-type heterogeneity, whether Wolbachia have different effects on cells at different stages of spermatogenesis or whether these effects are linked with CI remains unknown. Therefore, we used single-cell RNA sequencing to analyse gene expression profiles in adult male Drosophila testes that were infected or uninfected by Wolbachia . We found that Wolbachia significantly affected the proportion of different types of germ cells and affected multiple metabolic pathways in germ cells. Most importantly, Wolbachia had the greatest impact on germline stem cells, resulting in dysregulated expression of genes related to DNA compaction, and Wolbachia infection also influenced the histone-to-protamine transition in the late stage of sperm development. These results support the HM model and suggest that future studies on Wolbachia -induced CI should focus on cells in the early stages of spermatogenesis.